Women and Natural Resource Management A Conceptual Analysis - Nanda, Swati Sucharita (National Geographical Journal of India, 2022)
Conflicts over natural resources are endemic to developing countries. As conflicts over natural resources reach new heights, newer forms of interest groups make their presence felt. One such group has been that of women whose daily lives are closely interconnected with natural resources and their preservation. Today, they, on their own as well as due to development efforts, have been in the forefront of debate on natural resource. Women’s relationship with Natural Resource Management (NRM) has been wellestablished in the development literature though there still exists a lot of confusion regarding the exact nature of such relationship. A holistic understanding of exact nature of linkage between women and NRM remains a mirage due to the tendency of different disciplines to treat the issue from their respective narrow perspectives. A holistic understanding of this relationship would require nothing less than putting women at the centre of the discourse on NRM without regards to the disciplinary boundaries. A feminist perspective has analytical strength to provide an avant-garde understanding of women’s relationship with NRM. In view of this, the paper begins with a discussion of the concept and thrust areas natural resource management followed by a critical examination of women relationships with NRM. Finally, the paper tries to locate the role of women in the NRM processes.